A Five-Part Seminar Series on USMLE Step 1 Preparation - Roy Strowd; Ann Lambros (Association of American Medical Colleges, 2010)
Abstract Introduction Medical school curricula are specifically designed to address issues related to content competency and knowledge-based preparation. The USMLE Step 1 examination is a major indicator of basic science content competency. Studies have shown, and students at our institution have indicated, that success on this examination requires efficient preparation and adequate student confidence in addition to content competency. This course is designed to address issues relating to student guidance, support, early awareness, and confidence. Methods In this resource, we provide a session-by-session manual and accompanying PowerPoint presentations for the development and implementation of a five-part seminar series offered during the first 2 years of medical school. The series is composed of five 1-hour seminars, beginning with a short presentation followed by an interactive discussion between first- and second-year medical students. Two sessions are held in the first year and focus on general topics addressing the personalization of study strategies. Three sessions are held in the second year and focus more specifically on planning and preparation strategies for the USMLE Step 1 examination. Results In the first 2 years of implementation, we have observed profound improvement in student confidence. Course participants praised the series for addressing important stressors in medical education and providing not only helpful solutions to these challenges but also an interactive environment for communicating with upperclassmen. Students have found communication with these colleagues to be extremely beneficial. In a review survey of the course, with over 70% of students responding, more than 80% of students agreed or strongly agreed that the course was helpful in providing guidance for early USMLE Step 1 study planning. Discussion This course complements existing medical school curricula and provides formal student guidance on early planning and preparation strategies for success throughout medical school, with particular emphasis on the USMLE Step 1 examination. The course is designed to impact all medical students; however, particular focus is aimed at students who may be at risk of poor performance. We encourage the implementation of this course in existing medical school curricula.